2016
DOI: 10.1002/jssc.201600209
|View full text |Cite
|
Sign up to set email alerts
|

Ultra high performance liquid chromatography with tandem mass spectrometry screening and mutagenicity evaluation of photodegradation products of Carmoisine (E122) dye in a beverage

Abstract: The present study deals with the separation and identification of the photodegradation products formed when a commercial soft drink containing Carmoisine (E122) dye was exposed to natural sunlight. An ultra high performance liquid chromatography with quadrupole time-of-flight tandem mass spectrometry method was developed and validated to identify the unknown species of E122. During the study, it was observed that the dye decolourizes rapidly in beverage when compared to model standard solutions. The sunlight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The OECD Test Guidelines of Chemicals and Principles of Good Laboratory Practices are internationally recognized standards to ensure reliable, high-quality data and avoid duplicate testing (OECD, 2021). These guidelines 1982,1984,1986 No Artificial azo dyes were evaluated in in vitro (Yamjala et al, 2016;Floriano et al, 2018) and in vivo (Tanaka et al, 2008;Honma, 2015;Bastaki et al, 2017aBastaki et al, , 2017bJoshi & Pancharatna, 2018;Bastaki et al, 2019;Jiang et al, 2020) models, and 40% of the studies evaluated the toxicological effects of tartrazine; 30% of Sunset Yellow FCF, Allura Red AC, and carmoisine; and 10% of amaranth. However, no studies of the other dyes evaluated in this review following OECD guidelines were found.…”
Section: Hazard Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The OECD Test Guidelines of Chemicals and Principles of Good Laboratory Practices are internationally recognized standards to ensure reliable, high-quality data and avoid duplicate testing (OECD, 2021). These guidelines 1982,1984,1986 No Artificial azo dyes were evaluated in in vitro (Yamjala et al, 2016;Floriano et al, 2018) and in vivo (Tanaka et al, 2008;Honma, 2015;Bastaki et al, 2017aBastaki et al, , 2017bJoshi & Pancharatna, 2018;Bastaki et al, 2019;Jiang et al, 2020) models, and 40% of the studies evaluated the toxicological effects of tartrazine; 30% of Sunset Yellow FCF, Allura Red AC, and carmoisine; and 10% of amaranth. However, no studies of the other dyes evaluated in this review following OECD guidelines were found.…”
Section: Hazard Characterizationmentioning
confidence: 99%
“…Artificial azo dyes were evaluated in in vitro (Yamjala et al., 2016; Floriano et al., 2018) and in vivo (Tanaka et al., 2008; Honma, 2015; Bastaki et al., 2017a, 2017b; Joshi & Pancharatna, 2018; Bastaki et al., 2019; Jiang et al., 2020) models, and 40% of the studies evaluated the toxicological effects of tartrazine; 30% of Sunset Yellow FCF, Allura Red AC, and carmoisine; and 10% of amaranth. However, no studies of the other dyes evaluated in this review following OECD guidelines were found.…”
Section: Risk Assessment Of Artificial Azo Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Most of the studies in the literature describe the dye mineralisation process and very few have reported the characterization of the degradation products of azo dyes in beverages along with in vitro mutagenicity studies. 17,18 The Ames, or bacterial reverse mutation assay, is one of the most widely used in vitro tests for assessing the mutagenicity of chemicals. The bacterial strains used in this assay have preexisting mutations in various genes with histidine, or tryptophan (in case of Escherichia coli) operon, which code for the biosynthesis of the amino acid histidine or tryptophan.…”
Section: Introductionmentioning
confidence: 99%